Data-Driven Retrospective Correction of B1 Field Inhomogeneity in Fast Macromolecular Proton Fraction and R1 Mapping - Yarnykh, Vasily L. (IEEE transactions on medical imaging, 2021)
Correction of B_{1} field non-uniformity is critical for many quantitative MRI methods including variable flip angle (VFA) T_{1} mapping and single-point macromolecular proton fraction (MPF) mapping. The latter method showed promising results as a fast and robust quantitative myelin imaging approach and involves VFA-based R_{1}=1/T_{1} map reconstruction as an intermediate processing step. The need for B_{1} correction restricts applications of the above methods, since B_{1} mapping sequences increase the examination time and are not commonly available in clinics. A new algorithm was developed to enable retrospective data-driven simultaneous B_{1} correction in VFA R_{1} and single-point MPF mapping. The principle of the algorithm is based on different mathematical dependences of B_{1} -related errors in R_{1} and MPF allowing extraction of a surrogate B_{1} field map from uncorrected R_{1} and MPF maps. To validate the method, whole-brain R_{1} and MPF maps with isotropic 1.25 mm 3 resolution were obtained on a 3 T MRI scanner from 11 volunteers. Mean parameter values in segmented brain tissues were compared between three reconstruction options including the absence of correction, actual B_{1} correction, and surrogate B_{1} correction. Surrogate B_{1} maps closely reproduced actual patterns of B_{1} inhomogeneity. Without correction, B_{1} non-uniformity caused highly significant biases in R_{1} and MPF ( P < 0.001 ). Surrogate B_{1} field correction reduced the biases in both R_{1} and MPF to a non-significant level ( 0.1\le {P}\le 0.8 ). The described algorithm obviates the use of dedicated B_{1} mapping sequences in fast single-point MPF mapping and provides an alternative solution for correction of B_{1} non-uniformities in VFA R_{1} mapping.